Sequence variability of the β Tubulin isotype-1 genes in benzimidazole resistant strains of Haemonchus contortus, a nematode parasite of sheep - Dyah Haryuningtyas; wayan T Artama; Widya Asmara (Jurnal Ilmu Ternak dan Veteriner, 2006)
Resistance to benzimidazole at a population of gastrointestinal nematode, especially Haemonchus contortus is a widespread problem. Therefore, anthelmintic will not effective anymore. Benzimidazole resistance in nematode has been shown to be heritable and defined as an increase in frequency of individual worms able to drug tolerate. In Indonesia resistance to anthelmintic albendazole has been reported on sheep in district of Bogor, Kuningan, Kendal and province of Yogyakarta. Molecular mechanism of resistance to benzimidazole on nematode and fungi related to single gene which code ß tubulin. The aim of this research is to determine a genetics variability of isotype-1 ß tubulin genes from Indonesian strain of H. contortus which resistant to benzimidazole. Sequencing were carried out at a 520 bp fragment of the isotipe-1 ß tubulin gene of six H. contortus resistant strain from four sheep from SPTD Trijaya farm, district of Kuningan, West Java; UPTD Pelayanan Kesehatan Hewan farm, district of Bantul, Yogyakarta respectively. One H. contortus susceptible strains as a control come from farmer from Cicurug, district of Sukabumi, West Java. Results indicated that there are genetics variability of  fragment isotype-1 ß tubulin genes from H. contortus from UPTD Pelayanan Kesehatan Hewan farm, Bantul, Yogyakarta (H1, H2, and C2). There are no genetics variability in the fragment gene of H. contortus resistant strain from SPTD Trijaya farm, Kuningan, West Java (Kn1, Kn2 and K1). Genetic variability occur between 2 isolate from different location. Key Words: Haemonchus contortus, Benzimidazole, Isotype 1 β-tubulin Gene, Sequencing